Pharcidopsyche novemplicata, a curious new genus and species of the Psychidae, representing new subfamily Pharcidopsychinae (Lepidoptera, Tineoidea) - Saigusa, Toyohei; Sugimoto, Mika (Zootaxa, 2025)
The psychid genus Pharcidopsyche Saigusa et Sugimoto, gen. nov. and its type species, Pharcidopsyche novemplicata Saigusa et Sugimoto, sp. nov. (Lepidoptera, Psychidae) are described based on the adults, larvae and larval case from Sabah, Borneo. Pharcidopsychinae, subfam. nov. is established for the new genus. The adult and larval morphology, larval case and biology of the type species are described.